Screening of nutritional factors through a Plackett-Burman experimental design during the solubilization of Ca3(PO4)2 by Penicillium hispanicum - Wilberth Chan Cupul; Dulce Guadalupe Jiménez Barrera; Roberto Lezama Gutiérrez; Esaú Ruiz Sánchez; Octavio Pérez Zamora; Marco Tulio Buenrostro Nava; Gilberto Manzo-Sánchez (Acta Agronómica)
Phosphorus plays a fundamental role in plant metabolic processes.  Lack of phosphorus in agricultural soils is compensated with chemical fertilizers, which increase the cost of production and contaminate the environment.  One approach to avoid this situation is the use of P-solubilizing fungi as biofertilizers.  In this study, the solubilization of Ca3(PO4)2 by five native soil-borne micromycetes (SBM) isolated from the rhizosphere of Carica papaya plants was evaluated.  The significant nutritional factors involved in the solubilization of Ca3(PO4)2 by Penicillium hispanicum were determined through a Plackett-Burman experimental design (PBED). Both Penicillium SP1 (108.5 mg/L) and P. hispanicum (106.5 mg/L) solubilized 100% of Ca3(PO4)2 at six days of culture.  All studied SBM decreased the pH of the culture mediumfrom 4.15 (control) to <2.45.  The PBED revealed that the solubilization of Ca3(PO4)2 by P. hispanicum was significantly influenced (P < 0.05) by low values of MnSO4 (0.002 g/L), (NH4)2SO4 (0.25 g/L) and pH (4.0) and a high amount of Ca3(PO4)2 (0.75 g/L).  Total protein content was influenced significantly (P <0.05) by low amounts of glucose (5.0 g/L), yeast extract (0.25 g/L), inoculum (1×105 conidia/mL) and pH (4.0) and high amounts of MgSO4 (0.15 g/L), FeSO4 (0.003 g/L) and Ca3(PO4)2 (0.75 g/L).  Meanwhile, biomass production was significantly (P < 0.05) influenced by a high level of glucose (15.0 g/L) and inoculum amount (1×107 conidia/mL).  In conclusion, P. hispanicum is a good candidate for further field experiments to test Ca3(PO4)2 solubilization in poor soils that lack Cand N sources.